Paleoearthquakes Constrained by Stratigraphic Sequences of Different Drainages Since Late Pleistocene: A Case Study Along the Gulang Fault, NE Tibetan Plateau - Liang, Shumin; Zheng, Wenjun; Zhang, Dongli; Chen, Gan; Duan, Lei; Yang, Jingjun; Peng, Hui; Sun, Xin (Frontiers in Earth Science, 2021)
Paleoearthquake data obtained from fault trenching are essential for rebuilding the rupture history and understanding the rupture behavior of active faults. However, due to the lack of attention to stratigraphic sequences, the usual multiple trench constraining method may result in uncertainties of paleoearthquake sequences. In this study, we proposed an improved constraining method to generate stratigraphic sequences from multiple trenches of different drainages to obtain a paleoearthquake sequence of the Gulang fault. Single-trench stratigraphic sequences were built up by nineteen trenches excavated along the fault. Based on stratigraphic characteristics, we found the strata sedimented around the fault were derived from five drainages. The single-trench sequences were divided into five drainages to establish the composite sequence of multiple trenches through the correlation of stratigraphic units. Meanwhile, we used high-quality event indicators to pick out very likely earthquakes. Coupled with the dating samples, the events were used to determine the earthquake horizons in the composite sequence and to constrain the numbers and ages of events in each drainage. After combining the event sequences, six paleoearthquakes were determined along the Gulang fault since the late Pleistocene. Their occurrence timings are 13700–10400, 10400–10200, 8560–7295, 5825–4810, 4285–3200, and 2615–2240 a B.P.. And their different rupture scenarios indicate that the fault might be composed of two rupture segments.